2014
DOI: 10.1111/1574-6941.12359
|View full text |Cite
|
Sign up to set email alerts
|

Structure of hydrocarbonoclastic nitrate-reducing bacterial communities in bioturbated coastal marine sediments

Abstract: The organisation of denitrifying microorganisms in oil-polluted bioturbated sediments was investigated in mesocosms under conditions as closer as possible to that observed in the environment. Molecular and culture-dependent approaches revealed that denitrifying Gammaproteobacteria were abundant in oil-polluted and bioturbated sediments suggesting that they may play a key role in hydrocarbon degradation in the environment. T-RFLP and gene libraries analyses targeting nirS gene showed that denitrifying microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…Phylogenetic analysis showed that a large proportion of the unique OTUs matched with uncultured environmental nirS assemblages. The majority of the closely matched sequences in the GenBank were retrieved from sediment e n v i r o n m e n t s , i n c l u d i n g H a i h e R i v e r e s t u a r y (KC106788), Yangtze estuary (KF363218; EU236006; KM892169; EU235754) (Zhang et al 2014;Zheng et al 2015), Bahia del Tobari estuary (KC614247), San Francisco Bay estuary (GQ453730) (Mosier and Francis 2010), Bohai Gulf (JN257854), East Pacific sea (GU348415), coastal sea in France (KJ640012) (Stauffert et al 2014), as well as coastal regions in Baltic sea (DQ072204) (Hannig et al 2006) and the South Pacific (AJ811468) (Castro-Gonzalez et al 2005). The nirS gene sequences of cluster IX were closely related to the cultivated denitrifiers of Proteobacteria Pseudomonadales (CP000304) (90 % identity) (Yan et al 2008).…”
Section: Community Composition and Distribution Of Nirs-encoding Bactmentioning
confidence: 99%
“…Phylogenetic analysis showed that a large proportion of the unique OTUs matched with uncultured environmental nirS assemblages. The majority of the closely matched sequences in the GenBank were retrieved from sediment e n v i r o n m e n t s , i n c l u d i n g H a i h e R i v e r e s t u a r y (KC106788), Yangtze estuary (KF363218; EU236006; KM892169; EU235754) (Zhang et al 2014;Zheng et al 2015), Bahia del Tobari estuary (KC614247), San Francisco Bay estuary (GQ453730) (Mosier and Francis 2010), Bohai Gulf (JN257854), East Pacific sea (GU348415), coastal sea in France (KJ640012) (Stauffert et al 2014), as well as coastal regions in Baltic sea (DQ072204) (Hannig et al 2006) and the South Pacific (AJ811468) (Castro-Gonzalez et al 2005). The nirS gene sequences of cluster IX were closely related to the cultivated denitrifiers of Proteobacteria Pseudomonadales (CP000304) (90 % identity) (Yan et al 2008).…”
Section: Community Composition and Distribution Of Nirs-encoding Bactmentioning
confidence: 99%
“…Ribosomal or denitrifying genes affiliated to the genus Marinobacter have been identified in oil spill simulation mesocosms with marine coastal sediment (Stauffert et al 2014), estuarine sediment (Gray et al 2011), or m a n g r o v e s e d i m e n t ( d o s S a n t o s e t a l . 2 0 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Among toxic substances contained in aloin, polycyclic aromatic hydrocarbons (PAHs) are known by their harmful effect once in the ecosystem; they are one of the most common groups with known or potential toxic properties [8]. PAHs are a substantial threat to ecological function and soil biodiversity [9].The response of microbial communities to chronic inputs of PAHs [10,11,12] has received little attention compared to the effect of acute contaminations [13,14,15]. Indeed, previous studies demonstrated that PAH change bacterial communities structure and diversity [16,17,18].…”
Section: Introductionmentioning
confidence: 99%